Collective action in ant control - Ravnborg, Helle Munk; de la Cruz, Ana Milena; del Pilar Guerrero, Maria; Westermann, Olaf (International Food Policy Research Institute, 2000)
Leaf-cutting ants (Atta. cephalotes) represents a serious problem to farmers in many parts of Latin America and accounts of ants eating up a whole cassava plot or destroying one or more fruit trees overnight are not uncommon. Ants do not respect farm boundaries. Therefore, farmers who control anthills on their own fields might still face damage on their crops caused by ants coming from neighboring fields where no control measures are taken. In that sense, crop damage caused by leaf-cutting ants constitutes a transboundary natural resource management problem which, in addition to technical interventions, requires organizational interventions to ensure a coordinated effort among farmers to be solved. This paper reports on a research effort initiated by CIAT and implemented jointly between CIAT and farmers in La Laguna - a small community in the Andean Hillsides of Southwestern Colombia. The objective of the research effort was two-fold: i) to identify low cost technical options for ant control, and ii) to analyze and visualize the transboundary nature of the ant control problem and thus identify organizational options to enable collective or coordinated ant control.